A Contribution to the Flora of North Eastern Madhya Pradesh - Sebastine, K. M.; Balakrishnan, N. P. (Indian Forester, 1963)
The article deals with the flora of the North Eastern Regions of Madhya Pradesh. Botanical explorations were made at various places during the different seasons of the year and in all a total of 79 families represented by 279 genera and 382 species of flowering plants and 7 families represented by 11 genera and 15 species of non-flowering plants are found occurring in this region and they are enumerated.